Pelaksanaan Keselamatan dan Kesehatan Kerja Terhadap Perlindungan Hukum Bagi Pekerja Wanita Yang Bekerja Pada Malam Hari - Mariza, Siska; Setiady, Tri (Universitas Sang Bumi Ruwa Jurai, 2024)
Today, employment issues are still vital. OHS coverage for women workers is one of the main factors contributing to various problems in the workplace. Employers often discriminate against workers, especially women, compromising their right to health insurance and job security. It is important to provide adequate insurance against workers' privileges as they are a vulnerable group compared to managers who have a more prominent and influential position. This is guaranteed by Article 27 paragraph 2 of the 1945 Constitution which states that every Indonesian citizen has the privilege of honorable work. This exploration utilizes legal and administrative norms to look at the legal security for women OHS workers and the constraints that exist. The findings of this study show that legal protection of OSH is overall adequate; however, there are still some aspects that are less than optimal, such as women transportation workers who are required to work at night. Women workers lack understanding of occupational safety and security, and employers violate regulations for their own benefit. If their rights as employees are violated